2024
DOI: 10.1007/s11065-024-09638-2
|View full text |Cite
|
Sign up to set email alerts
|

Transparency in Cognitive Training Meta-analyses: A Meta-review

Alejandro Sandoval-Lentisco,
Rubén López-Nicolás,
Miriam Tortajada
et al.

Abstract: Meta-analyses often present flexibility regarding their inclusion criteria, outcomes of interest, statistical analyses, and assessments of the primary studies. For this reason, it is necessary to transparently report all the information that could impact the results. In this meta-review, we aimed to assess the transparency of meta-analyses that examined the benefits of cognitive training, given the ongoing controversy that exists in this field. Ninety-seven meta-analytic reviews were included, which examined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…To our knowledge, these findings provide the first field-wide examination of the prevalence and practice of preregistration in psychology meta-analyses. Other studies have provided a range of estimates (2%-36%) for the prevalence of meta-analysis preregistration in various sub-fields of psychology (López-Nicolás et al, 2022;Polanin et al, 2020;Sandoval-Lentisco et al, 2024), but direct comparison is difficult because of differences in time-frame. Comparing the prevalence measure in the current study (27%) to a recent field-wide estimate (8%) for the prevalence of preregistration in empirical psychology (Hardwicke et al, in preparation), suggests that preregistration is more common for meta-analyses relative to empirical studies in general in psychology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, these findings provide the first field-wide examination of the prevalence and practice of preregistration in psychology meta-analyses. Other studies have provided a range of estimates (2%-36%) for the prevalence of meta-analysis preregistration in various sub-fields of psychology (López-Nicolás et al, 2022;Polanin et al, 2020;Sandoval-Lentisco et al, 2024), but direct comparison is difficult because of differences in time-frame. Comparing the prevalence measure in the current study (27%) to a recent field-wide estimate (8%) for the prevalence of preregistration in empirical psychology (Hardwicke et al, in preparation), suggests that preregistration is more common for meta-analyses relative to empirical studies in general in psychology.…”
Section: Discussionmentioning
confidence: 99%
“…López-Nicolás et al (2022) found that 19% of a random sample of 100 meta-analyses on clinical psychological interventions published between 2000 and 2023 were preregistered. Sandoval-Lentisco et al, (2024) found that 36% of 97 meta-analyses on cognitive training published between 1997 and 2023 (of which 40 were published from 2020) were preregistered. Currently, there is no available estimate for the prevalence of preregistered meta-analyses across the entire field of psychology.…”
Section: Prevalence and Practice Of Preregistration In Psychology Met...mentioning
confidence: 99%